Cepharanthine Suppresses Herpes Simplex Virus Type 1 Replication Through the Downregulation of the PI3K/Akt and p38 MAPK Signaling Pathways - Liu, Yao; Chen, Li; Liu, Wenjun; Li, Dan; Zeng, Jiuseng; Tang, Qiong; Zhang, Yuexin; Luan, Fei; Zeng, Nan (Frontiers in Microbiology, 2021)
Cepharanthine (CEP) is a naturally occurring isoquinoline alkaloid extracted from Stephania cepharantha Hayata. Although its underlying molecular mechanism is not fully understood, this compound has been reported as a promising antiviral drug. In the present study, we explored the anti-HSV-1 effects and the underlying molecular mechanisms of CEP in vitro. Our results showed that CEP could significantly inhibit the formation of plaque and the expression of viral proteins and exhibit a general suppression of replication-associated genes. While HSV-1 infection increased the expressions of phosphoinositide 3-kinase (PI3K), Protein Kinase B (Akt), and p38 mitogen-activated protein kinase (p38 MAPK) in host cells, CEP was effective indirectly inhibiting phosphorylation levels of the targets in PI3K/Akt and p38 MAPK signaling pathways. Moreover, CEP markedly decreased G0/G1 phase and increased G2/M phase cells, and decreased the expression of cyclin-dependent kinase1 (CDK1) and cyclinB1 in a dose-dependent manner. Additionally, CEP increased apoptosis in infected cells, reduced B-cell lymphoma-2 (Bcl-2) protein levels, and increased the protein levels of Bcl-associated X protein (Bax), cleaved-caspase3, and Nuclear IκB Kinaseα (IκBα). Collectively, CEP could arrest the cell cycle in the G2/M phase and induce apoptosis in infected cells by inhibiting the PI3K/Akt and p38 MAPK signaling pathways, hence further reducing HSV-1 infection and subsequent reproduction.